STUDI INTERAKSI SENYAWA GOLONGAN CANNABINOID TERHADAP RESEPTOR CANNABINOID TIPE 2 - Oktavia Citra, Dewi
Cannabinoids are compounds isolated from the Cannabis sativa plant that can interact with cannabinoid receptors in the body and cause pharmacological effects. One of the cannabinoid receptors is cannabinoid receptor type 2 (CB2 receptor). This study aims to study new isolated cannabinoid compounds that can interact with CB2 receptor through in silico method so that they can be further tested and developed as drugs. Prior to any simulation, literature review is carried out on test and standard compounds used. Three-dimensional structure of both test and standard compounds was modelled using Avogadro 1.2.0 and GaussView 5.0.8 and optimized using Gaussian09. Crystal structure of CB2 receptor was retrieved from Protein Data Bank. Docking simulation was performed using AutoDock 4.2. The results of docking simulation were then analyzed with BIOVIA Discovery Studio Visualizer 2021 and followed by molecular dynamics simulation using AMBER16 program. The calculation of the binding free energy value was carried out using Molecular Mechanics Poisson-Boltzmann Surface Area (MM-PBSA) method. The results of the interaction study showed that the interacting amino acid residues were quite varied but standard and test compounds occupy the same binding pocket so it can be predicted that both have similar activities. The best binding free energy of the CB2 receptor complex with the test compounds was shown by compounds 18, 14, and 13 with binding free energy values are ?147,798 kJ/mol, ?136,143 kJ/mol, and ?130,038 kJ/mol, respectively. Based on the position of the binding pocket and binding free energy value, five of the six priority test compounds namely compounds 18, 14, 13, 19, and 16 were proposed to be further tested in vitro and in vivo.